Evaluation of quality of life using Sinonasal Outcome Test-22 among patients with chronic rhinosinusitis postendoscopic sinus surgery: A preliminary report - Abdulrahman O Afolabi; Kenechukwu Uche-Okonkwo; Nasiru Olalekan Shittu; Samuel O Ayodele; Nafeesat O Busari; Segun Segun-Busari; H K Omokanye; Saad O Idris; Biodun S Alabi; Adekunle D Dunmade; Foluwasayo E Ologe (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: The background of this study was to assess the quality of life (QoL) of patients with chronic rhinosinusitis (CRS) before and after endoscopic sinus surgery Sinonasal Outcome Test-22 (SNOT-22). MATERIALS AND METHODS: This was an observational prospective cohort study carried out at the Ear, Nose and Throat Department of Kogi State Specialist Hospital, Lokoja, and University of Ilorin Teaching Hospital, Ilorin. Both of which are tertiary-level hospitals in North-Central Nigeria offering advanced rhinology services after ethical approval was obtained. The total score for each subject was derived from the 22-item psychometrically validated self-administered SNOT-22 questionnaire. Lower scores postoperatively represent better health-related QoL (HRQOL). RESULTS: A preliminary report of 40 consecutive patients with rhinosinusitis were enrolled. There were 19 males and 21 females aged between 16 and 80 years (mean age: 34.95 ± 2.69 years). There was a significant improvement in SNOT-22 scores from the preoperative period: 37-88 (mean: 67.45 ± 15.10) to 22-43 (mean: 31.73 ± 5.61) 6 weeks after surgery, giving a percentage improvement of 52.97% (P = 0.0002), thus statistically significant. CONCLUSION: SNOT-22 tool is a valuable tool to evaluate the HRQOL of patients with CRS and endoscopic sinus surgery as surgical intervention improves the HRQOL of patients with reduction in the mean score of all items in the SNOT-22 in the postoperative state compared to the preoperative state.